Analisis Pengaruh Job Insecurity Dan Kompensasi Terhadap Kinerja Karyawan Yang Dimediasi Oleh Kepuasan Kerja Pada Toserba Matahari Sragen - Yola Putri Januarti Mangunsong; Irmawati Irmawati (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this study was to investigate the relationship between job insecurity and employee performance, the relationship between job satisfaction and compensation, the relationship between job insecurity and employee performance mediated by compensation, and the relationship between job insecurity and employee performance tested by satisfaction at work. Quantitative research techniques were used to conduct this research. Using the SmartPLS software, a route analysis approach was applied in this investigation. The validity and dependability of the analytic test were evaluated using a measurement model (outer model), and the causality test or predictive model hypothesis was evaluated using a structural model (inner model). As research findings show, job uncertainty substantially reduces job fulfillment. Compensation has a significant impact on job satisfaction. Job insecurity has a significant negative impact on employee performance. Worker execution is basically influenced by salary. Job satisfaction has a significant impact on employee performance. Employee performance is indirectly mediated by job satisfaction when compared to compensation and job insecurity.